2012
DOI: 10.1007/s00128-012-0777-6
|View full text |Cite
|
Sign up to set email alerts
|

Residues of Organochlorine Pesticides in Water and Suspended Particulate Matter from Xiangshan Bay, East China Sea

Abstract: Residual levels, distribution and possible sources of organochlorine pesticides (OCPs) in nine water column and suspended particulate matter (SPM) samples collected from Xiangshan Bay, East China Sea were investigated. Total OCPs concentrations in water column and SPM ranges from 2.88 to 34.72 ng/L and 2.47 to 29.94 ng/L, respectively, which exceed the US Environmental Protection Agency regulatory limits. Moreover, low ratio of α-HCH/γ-HCH and high ratios β- and γ-HCH suggested the cocktail input pattern of fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 12 publications
0
12
0
3
Order By: Relevance
“…Xiangshan and Sanmen Bays are important sea cultivation regions in Ningbo and are typical semi-enclosed bays [36]. Xiangshan Bay is a long and narrow bay, bordering Hangzhou Bay in north and adjacent to Sanmen Bay in the south and the Zhoushan Archipelago in the east [37,38]. The tidal waves that result from the prevailing wind coming from the east of East China Sea most of the year become stationary waves because of being blocked by the Liuheng Island, one of Zhoushan Archipelago in the mouth of Xiangshan Bay [37].…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Xiangshan and Sanmen Bays are important sea cultivation regions in Ningbo and are typical semi-enclosed bays [36]. Xiangshan Bay is a long and narrow bay, bordering Hangzhou Bay in north and adjacent to Sanmen Bay in the south and the Zhoushan Archipelago in the east [37,38]. The tidal waves that result from the prevailing wind coming from the east of East China Sea most of the year become stationary waves because of being blocked by the Liuheng Island, one of Zhoushan Archipelago in the mouth of Xiangshan Bay [37].…”
Section: Study Areamentioning
confidence: 99%
“…For a long time, promoting the common development of industry, tourist and organic agriculture along the coast based on its resource advantages has driven the land use changes of Sanmen Bay coastal zone. A regional development plan has been formulated for the development of the three relatively independent economic regions based on the administrative division and the characteristic resources of the three bays [38][39][40]. Eventually, the south partial silting-up action that resulted from tide and wind created the splendid Hemudu Culture and developed the famous Sanbei Riffle with a width of 2-6 km.…”
Section: Study Areamentioning
confidence: 99%
“…Among the identified organic impurities present in wastewater, micro-pollutants are a significant group. This group includes organochlorine pesticides and polycyclic aromatic hydrocarbons (PAH), polychlorinated biphenyls (PCBs), di-2-ethylhexyl phthalate (DEHP) and polychlorinated dibenzodioxins and dibenzofurans (PCDD and PCDF) [Nawirska 2007;Li et al 2012;Grotowska et al 2018]. This is mainly related to the wide application of chemical plant protection products in agriculture in order to obtain more abundant crops of better quality [Ignatowicz 2008[Ignatowicz , 2009Łozowicka 2010;Głowacki et al 2014].…”
Section: Introductionmentioning
confidence: 99%
“…Eastern China has the highest levels of pesticide application in the country [ Li et al , ; Zhang et al , ], and Zhejiang and Jiangsu Provinces ranked top in pesticide consumption per unit area from 1985 to 1991 [ Wang et al , ]. Recent surveys relating to DDT and HCH levels in coastal eastern China, such as those in air [ Ji et al , ; Wu et al , ], water [ Li et al , ], sediments [ Hu et al , ; Liu et al , ; Tang et al , ], and suspended particulate matter [ Li et al , ; Liu et al , ], indicated that the YRE and adjacent ECS are seriously polluted compared to other coastal areas off China. Results from source analyses indicated that input from the Yangtze River is an important source of HCH and DDT in water and sediments, and the continental outflow driven by the East Asian Monsoon brings large quantities of particulate HCH and DDT to the YRE, especially in winter.…”
Section: Introductionmentioning
confidence: 99%